The Use of Augmented Reality Technology in Efforts to Promote Library Books - Andre Kurniawan Pamudji (Soegijapranata Catholic University, 2024)
The abstract of the article is about the use of Augmented Reality technology to promote physical books and increase interest in reading among the millennial generation. The author highlights the challenge faced by libraries in the current era, which is the lack of interest in reading among young people, as reported by data from the Program for International Student Assessment (PISA) in 2019. The author argues that many books designed for children and young people are perceived as unappealing and lack attractive visual elements, which affects their literacy. To address this issue, the author suggests the use of Augmented Reality technology, which combines the real and virtual world, to promote physical books and increase interest in reading. The author cites Snapchat, a popular social media application with over 332 million daily users, as an example of a software that can be used to implement Augmented Reality technology in promoting books.